Iron(III)-Mediated Rapid Radical-Type Three-Component Deuteration of Quinoxalinones With Olefins and NaBD4 - Li, Wanmei; Cai, Heng; Huang, Lin; He, Lei; Zhang, Yilan; Xu, Jun; Zhang, Pengfei (Frontiers in Chemistry, 2020)
Iron (III)-promoted rapid three-component deuteration of quinoxalinones with olefins and NaBD4 is reported for the first time, which provides a novel, economic and efficient method for the rapid synthesis of deuterated quinoxalinones. In this transformation, a radical pathway is involved according to the results of control experiments.